2016
DOI: 10.1002/eco.1722
|View full text |Cite
|
Sign up to set email alerts
|

Critical issues with cryogenic extraction of soil water for stable isotope analysis

Abstract: Cryogenic water extraction is the most widely used method to facilitate the laboratory removal of soil pore water for isotopic analysis. However, recent studies have suggested that cryogenic extraction conditions (extraction time, temperature, vacuum threshold) and physicochemical soil properties can influence extracted water isotopic signatures. Here, we argue that new work is needed to analyse the full extent of these effects on the extracted water isotopic composition. We illustrate this need with a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
244
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(259 citation statements)
references
References 51 publications
11
244
4
Order By: Relevance
“…However, recent experimental studies indicated potential for fractionation during the cryogenic extraction (Orlowski et al, 2016), probably induced by watermineral interactions (Oerter et al, 2014;Gaj et al, 2017a, b). The direct-equilibration method -as a potential alternative analysis method -we applied in our study was so far usually limited to study percolation processes (e.g., Garvelmann et al, 2012;Mueller et al, 2014;Sprenger et al, 2016a).…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…However, recent experimental studies indicated potential for fractionation during the cryogenic extraction (Orlowski et al, 2016), probably induced by watermineral interactions (Oerter et al, 2014;Gaj et al, 2017a, b). The direct-equilibration method -as a potential alternative analysis method -we applied in our study was so far usually limited to study percolation processes (e.g., Garvelmann et al, 2012;Mueller et al, 2014;Sprenger et al, 2016a).…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 99%
“…Including the isotopes of the bulk soil water, could allow for an improved conceptualization of the soil-plant-atmosphere interface, which is crucial for an adequate representation of evaporation and transpiration. Especially the marked differences of the evaporation signal within the first few centimeters of the soil depth will significantly affect the age distribution of transpiration (Sprenger et al, 2016c), evaporation (Soulsby et al, 2016a) or evapotranspiration (Harman, 2015;Queloz et al, 2015;van Huijgevoort et al, 2016).…”
Section: Vegetation Affects Critical Zone Evaporation Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of cryogenic vacuum distillation techniques has been questioned as the δ 18 O of extracted waters tends to be depleted in 18 O relative to the irrigation water when oven-dried soils that have been re-wetted are considered (Orlowski et al, 2016a;Sprenger et al, 2015). The extent of this depletion depends on soil properties.…”
Section: Soil Water Extraction and Analysismentioning
confidence: 99%
“…The naturally occurring vertical gradients of δD and δ 18 O in soil water provide similar information about plant water uptake depth from soils. A number of studies have used isotopes to characterize soil water movement in one location and thus one climatic regime (Orlowski et al, 2016b;Manzoni et al, 2013;Liu et al, 2011;Stumpp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%